(untitled) - IKA PUSPITA S, DHEWI (LATERNE, 2014)
Listening skill is one of four language skills that students should dominate. But in fact, many students are still having difficulties. One of the reason is less accustomed to listening native speakers. Of these issues, this research examines a problem of student learning outcomes with media E-learning WEC (Web Enhanced Course) that use of websites www.education.vic.gov.au/languagesonline to improve listening skill of Germanien. The research problem is “How do the results of students in the class X-Kimia Industri SMKN 1 Tuban in the Germanien listening skill with media E-Learning WEC (Web Enhanced Course)? ". The purpose is to know the improvement of student learning outcome class X-Kimia Industri SMKN 1 Tuban in listening skill after using media E-Learning WEC (Web Enhanced Course). The theory of Haughey about Web Enhanced Course (WEC) is the use of Internet to support the quality of learning in class, used in this research. This research is a qualitative research and data analysis ist descriptive. The subjects were students of class X-Kimia Industri SMKN 1 Tuban. The data of this research is the value of the test (pre-test and post-test) were done when using media E-learning WEC (Web Enhanced Course). The results showed an increase in the mean number of classes, from pre-test (pre-test) 57.07 to 87,99 at the end of the test (post-test). So it can be concluded that there is an increase student learning outcomes of class X-Kimia Industri SMKN 1 Tuban of listening skill after using media E-learning WEC (Web Enhanced Course). Keywords: media, E-learning WEC (Web Enhanced Course), listening skill